2005
DOI: 10.1016/j.clinbiomech.2004.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static flexion–relaxation on paraspinal reflex behavior

Abstract: Background.-Static trunk flexion working postures and disturbed trunk muscle reflexes are related to increased risk of low-back pain. Animal studies conclude that these factors may be related; passive tissue strain in spinal ligaments causes subsequent short-term changes in reflex. Although studies have documented changes in the myoelectric onset angle of flexion-relaxation following prolonged static flexion and cyclic flexion we could find no published evidence related to the human reflex response of the trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 42 publications
(49 reference statements)
6
59
0
Order By: Relevance
“…26 However, the results of this investigation were inconsistent with our previous results where reflex behavior was recorded from subjects following 15 minutes of continuous static flexionrelaxation. 6 In that study, we found a trend toward increased reflex gain immediately following prolonged static flexion-relaxation, which we concluded was consistent with the hyperexcitable EMG response found in animal research. 26 There are several possible explanations as to why our previous results differ from what we found here.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…26 However, the results of this investigation were inconsistent with our previous results where reflex behavior was recorded from subjects following 15 minutes of continuous static flexionrelaxation. 6 In that study, we found a trend toward increased reflex gain immediately following prolonged static flexion-relaxation, which we concluded was consistent with the hyperexcitable EMG response found in animal research. 26 There are several possible explanations as to why our previous results differ from what we found here.…”
Section: Discussionsupporting
confidence: 77%
“…A servomotor (Pacific Scientific, Rockford, IL) was used to elicit paraspinal reflexes according to protocol described in our previous work. 6 The motor provided a constant isotonic preload of 100 N that the subjects were instructed to resist by maintaining their upright seated posture. Pseudorandom stochastic force perturbations of ±75 N were superimposed on the preload (Figure 2A).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, there are a host of possible risk factors that can lead to impaired feedback control such as prolong flexion (Solomonow et al, 2003;Granata et al, 2005;Rogers and Granata, 2006), whole body vibration (Roll et al, 1980;Gauthier et al, 1981); and muscle wasting (Hides et al, 1996) to name a few. Delayed reflex responses are another source for controller impairment that has been associated with LBP (Radebold et al, 2000;Radebold et al, 2001;Reeves et al, 2005), and more recently has been shown to increase the risk of injury .…”
Section: Controller Related Impairmentmentioning
confidence: 99%
“…Granata et al investigated the influence of trunk posture [14], exertion direction [17,18], and preload [19] on spinal stability during flexion and extension exertions. Shirazi-Adl et al [20,21] developed a multi-degree of freedom finite element model to quantify the role of passive and active tissues in spinal stability.…”
Section: Introductionmentioning
confidence: 99%